Laryngeal biopsies: are we doing more, and why? A decade of results. Issue 1 (8th December 2015) - Lim, S; Sau, P; Cooper, L; McPhaden, A; MacKenzie, K
Abstract: Background: Over the last decade, we have observed an escalating trend in the number of laryngeal biopsies performed, despite the incidence of laryngeal cancer remaining constant. This study aimed to quantify the rate of laryngeal biopsies and record the indications. Method: A retrospective analysis of laryngeal biopsies performed in North Glasgow, Scotland, UK, between 2001 and 2010, was conducted. Results: From 2001 to 2010, 3902 laryngeal biopsies were carried out in North Glasgow. Histopathological results indicated the following diagnoses: squamous cell carcinoma, in 889 cases (23 per cent); dysplasia, in 986 cases (25 per cent); 'no tumour', in 913 cases (23 per cent); and benign pathology, in the remaining 1084 cases (28 per cent). There has been a significant increase in the number of biopsies performed after 2004, with the incidence of squamous cell carcinoma and benign disease remaining relatively static. Conclusion: It is hypothesised that organ preservation strategies, endoscopic resection in early stage laryngeal cancer and chemoradiotherapy in advanced head and neck cancer are responsible for the increase in laryngeal biopsies.